P292 Association of golimumab trough concentrations during maintenance with endoscopic and histologic remission in patients with ulcerative colitis. (21st January 2022) - Taxonera Samso, C; Fernández-Aceñero, M J; Olivares, D; Calvo, M; Casis, B; Bermejo, F; López Serrano, P; Iborra, M; Mesonero, F; Boscá Watts, M; Díaz del Arco, C; Vera, I; et al.
Abstract: Background: The aim of this study was to investigate the association of serum golimumab concentrations (SGC) during maintenance therapy in UC with clinical outcomes including endoscopic and histologic healing. Methods: This multicentre, cross-sectional cohort study included UC patients who had received at least 5 maintenance doses of golimumab. A colonoscopy was scheduled, and study-specific recto-colonic biopsies were taken for blind central histologic reading. Samples for trough SGC and anti-golimumab antibodies (AGA) were collected on the day of the scheduled golimumab administration closest to the colonoscopy. Definitions: clinical remission = partial Mayo score (PMS) ≤2 with no individual subscore >1, combined clinical-biochemical remission = PMS ≤2 + faecal calprotectin <300 μg/g, endoscopic healing = Mayo endoscopic subscore of 0, deep remission = clinical remission + endoscopic healing, histologic remission = Geboes index ≤2.0, and disease clearance = clinical remission + endoscopic healing + histologic remission. Results: Fifty-two patients were included. The overall median SGC was 1.79 µg/ml (interquartile range [IQR] 0.87–2.79). Three patients (5.7%) had undetectable SGC together with positive AGA. With a median of 23 [IQR 15–32] months of golimumab therapy, 46 patients (88%) were in clinical remission, 26 (52%) had combined clinical-biochemical remission, 18 patients (35%) had both endoscopic healing and deep remission, 21 (40%) had histologic remission, and 14 (27%) had disease clearance. Median SGC were significantly higher in patients who were in clinical remission (2.01 versus 0.72 µg/mL, P =0.047) µg/mL, combined clinical-biochemical remission (2.21 versus 1.47 µg/mL, P =0.041), mucosal healing and deep remission (2.52 versus 1.47 µg/mL, P =0.003), histologic remission (2.33 versus 1.50 µg/mL, P =0.02), and disease clearance (2.52 versus 1.70 µg/mL, P =0.009), compared with those not meeting these criteria. (Figure 1) The higher SGC quartiles were associated with higher rates of mucosal healing ( P =0.005), and histologic remission ( P =0.006). (Figure 2) Receiver-operating characteristic analyses identified SGC thresholds [area under the curve] of 0.85 [0.76], 1.90 [0.65], 2.29 [0.75], and 2.29 [0.72] µg/mL be associated with clinical remission, combined remission, deep remission, and disease clearance, respectively. (Table 1) On multivariate analysis, body mass index ( P =0.021) and CRP level ( P =0.040) were linearly associated with lower SGC, and concomitant immunosuppressant with higher SGC ( P =0.47). (Table 2) Conclusion: We identified SGC thresholds during maintenance most closely associated with clinical outcomes including endoscopic and histologic healing. Higher SGC are needed to achieve increasingly stringent therapeutic targets.